Evidence of limited N2 fixation in the Southern Ocean - Shuai Gu; Hugo Berthelot; Yajuan Lin; Weiyi Tang; Julie Robidart; A. Murat Eren; Hugh W. Ducklow; Nicolas Cassar (Communications Earth & Environment)
Abstract Biological nitrogen fixation is an important source of new nitrogen, influencing ocean fertility and carbon uptake. While recently documented in Arctic waters, its role in the Southern Ocean remains uncertain. We measured nitrogen fixation along the Western Antarctic Peninsula and at Palmer Station over two austral summer months. Rates from 15N2 assay were below conservative detection limits but detectable under less stringent detection thresholds. Continuous acetylene reduction assay provided further support. nifH gene sequencing identified Gammaproteobacteria as the dominating identified diazotrophs, while Epsilonproteobacteria contributed disproportionally to nifH expression when putative nitrogen fixation was highest. Combined with environmental observations, we hypothesize that vertical water mixing resuspended sediments into the water column and contributed to the limited nitrogen fixation. Given the sporadic and low rates, further research is needed to determine whether nitrogen fixation plays a minor role or represents an overlooked process with biogeochemical significance in the Southern Ocean.